Sporadic Vestibular Schwannoma Size and Location Do not Correlate With the Severity of Hearing Loss at Initial Presentation - Brown, Alyssa; Early, Samuel; Vasilijic, Sasa; Stankovic, Konstantina M. (Frontiers in Oncology, 2022)
Vestibular schwannoma (VS) is a non-malignant intracranial neoplasm arising from the vestibular branch of the 8th cranial nerve; sensorineural hearing loss (SNHL) is the most common associated symptom. Understanding whether VS imaging characteristics at time of VS diagnosis can be associated with severity of VS-induced SNHL can impact patient counseling and define promising areas for future research. Patients diagnosed with VS at Massachusetts Eye and Ear (MEE) from 1994 through 2018 were analyzed if magnetic resonance imaging at VS presentation and sequential audiometry were available. Results were compared with original studies available in PubMed, written in English, on VS imaging characteristics and their impact on hearing in patients. A total of 477 patients with unilateral VS from the MEE database demonstrated no significant correlation between any features of tumor imaging at time of VS diagnosis, such as VS size, impaction or location, and any hearing loss metric. Twenty-three published studies on the impact of VS imaging characteristics on patient hearing met inclusion criteria, with six solely involving NF2 patients and three including both sporadic and NF2-related VS patients. Fifteen studies reported a significant relationship between SNHL and at least one VS imaging characteristic, however these trends were universally limited to NF2 patients or involved small patient populations, and were not reproduced in larger studies. Taken together, SNHL in sporadic VS patients is not readily associated solely with any tumor imaging characteristics. This finding motivates future studies to define how VS microenvironment and secreted molecules influence VS-induced SNHL.